Pendidikan Kristen dan Karakter - Merri Natalia Situmorang (JURNAL KADESI, 2021)
The basis of Christian ethics in living together and working is not in rules, but in God's unchanging character. As the image and likeness of God, humans have good social and relational relationships with one another. The problem in this research is that the damage to humans due to sin makes humans no longer able to have the character that comes from God in achieving their life goals and in living together. Humans face many challenges in life so that there is competition for millions of people in a place (Gen. 3: 17-19). Humans throw each other down, hate, jealousy, bribes, injustice happen everywhere. This research uses descriptive theoretical qualitative research methods through literature and biblical studies. The benefit of this research is that through the Christian Religious Education process, Christians are active in teaching and learning the truth of God's Word, teaching God's people that in Christ man is a new creation (Ephesians 2:10) to do good deeds. The conclusion in this research is that with a mind and conscience renewed by Christ, it is possible for humans to develop the world of creation and life together with honesty, holiness, justice and love. Man in Christ finds himself stronger and can bring honor to his Creator. God's character is reflected in the character life of Christians in fulfilling God's purposes. This Christian character cannot be obtained simply through shortcuts but can only be obtained through the process of Christian education.